The development and study of herbal composition for complex therapy of influenza A - A. Ali Alshami; A. V. Panov; S. A. Kedik; E. A. Amirgulova; E. N. Vetrova; E. A. Dorovskikh; T. Yu. Kovaleva (Разработка и регистрация лекарственных средств)
Introduction. Influenza type A is a socially significant infectious disease. Viral variability, mutations and reassortment make vaccination difficult. New drugs for specific therapy need to be developed because resistance to the existing drugs has appeared. A number of plant extracts have antiviral activity against the influenza type A virus, research is relevant in this area. The development of a species is also relevant, which has both specific antiviral activity and affects the symptom complex accompanying this disease.Aim. To develop a medicinal herbal collection for specific and symptomatic treatment of influenza type A.Materials and methods. There were considered 14 pharmacopoeial types of medicinal plant raw materials and 3 herbal compositions based on them. The studies of biologically active substances in raw materials were carried out according to the methods of the State Pharmacopoeia of Russian Federation, 15th edition. Determination of antiviral activity was carried out on Madin-Darby canine kidney cells (MDCK) culture using the hemagglutination reaction.Results and discussion. There were studied the quantitative content of the main groups of biologically active substances (polysaccharides, tannins, flavonoids and ascorbic acid) in 3 variants of herbal compositions (collection No.No. 1, 2 and 3) and decoctions based on them. The variant of the herbal composition with the maximum content of biologically active substances was established. Antiviral activity against the influenza A virus of two herbal compositions was demonstrated.Conclusion. The composition of the medicinal herbal collection is proposed, which is promising for complex therapy of influenza. The antiviral effect against the influenza virus type A has been proven.